Narrativas e experiências no âmbito do Programa Institucional de Bolsa de Iniciação à Docência (PIBID) Biologia da UFES : investigando as contribuições para a profissionalização docente - Rabelo, Daniely Bárbara Bollis (2017)
This study aims to understand how the PIBID program (Institutional Program of the Initiation to Teaching Scholarship), which is based on the articulation between the universitys (professors and graduates), and the basic education school. It was able to contribute to the professionalization process of undergraduate scholarship holders in Biological Sciences of the Federal University of Espírito Santo. This study also sought to know the indications of the development of teaching professionality from the experiences narrated by its scholars and former scholars, to understand the conception of teacher training that structures the PIBID Biology of UFES and to understand how the program contributes to the process of one of its Area Coordinators. For this, we conduct a qualitative research of narrative character: Antonio Nóvoa, Francisco Imbernón, and other authors, who consider the school as a formative space. We based our discussion about teacher education on theoretical works. Regarding the training of science teachers and the teaching and learning processes that involve the specific knowledge and practices of the area, we seek the contributions of Ana Maria de Carvalho and Daniel Gil-Pérez, Derek Hodson, Rosalind Driver, among others. For the production of the data, we conducted the narrative interview and used my memories. For analysis of the data, we are in the Discursive Textual Analysis (DTA). The narratives, as well as the memories, demonstrated that, from the participation in the PIBID, there was the recognition of "knowing" and "knowing how to develop" practical activities in the context of Science teaching as a fundamental professionalism of the science teacher. In addition, knowing how to diversify activities in the classroom, to contextualize the knowledge of the discipline with the students daily life, and to enhance the dialogical dimension in mediation were dimensions recognized by the PIBID participant, as fundamental for the formation and work of the science teacher. Moreover, the interpersonal relationship appears as an important teaching professionality for the process of students teaching and learning, as well as for learning about teaching.